IMPLEMENTASI KEBIJAKAN HARI BELAJAR GURU DALAM MENINGKATKAN PROFESIONALISME PENDIDIK DI KOMUNITAS BELAJAR SDN TROPODO KRIAN KABUPATEN SIDOARJO - Rudi Purwanto; Budi Purwoko; Mufarrihul Hazin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the implementation of the Ministry of Education, Culture, Research and Technology Policy Number 5684/MDM.B1/HK.04.00/2025 concerning Teacher Learning Day at SDN Tropodo Krian, Sidoarjo Regency. Using a descriptive qualitative approach, this study examines the implementation mechanism, supporting factors, obstacles, and impact of the policy on teacher professional development. Data were collected through participatory observation, in-depth interviews with 15 respondents (teachers, principals, and resource persons), and document analysis during the period February - April 2025. The findings show that the implementation of the policy has increased collaboration between teachers by 65%, developed learning innovations, despite facing challenges in time allocation and availability of resource persons. This study recommends strengthening the mentoring system and providing digital learning resources to optimize the program.